Geography physical geography : student guide - Dunn, Cameron; Witherick, Michael (Hodder Education Group, 2021)
Reinforce understanding throughout the course with clear topic summaries and sample questions and answers to help students target higher grades. Written by experienced subject experts Cameron Dunn and Michael Witherick, this Student Guide is divided into two key sections - content guidance, and sample questions and answers. Content guidance will: - Develop understanding of key concepts and terminology in key physical geography topics tectonic processes and hazards, landscape systems, processes and change (glaciated and coastal), the water cycle and water insecurity, and the carbon cycle and energy security. - Consolidate knowledge with 'knowledge check questions' at the end of each topic and answers in the back of the book. Sample questions and answers will: - Build understanding of the different question types, so that students can approach each question with confidence. - Enable students to target top grades in their exam paper with sample answers and commentary explaining exactly why marks have been awarded.